Looking for Asian America : An Ethnocentric Tour by Wing Young Huie - Huie, Wing Young, 1955- (Book collections on Project MUSE., 2007)
In search of contemporary Asian America, celebrated photographer Wing Young Huiethe only member of his family not born in Chinatraveled with his wife, Tara, through nearly forty states to explore and document the funny, touching, and sometimes strange intersection of Asian American and American cultures. Looking for Asian America illustrates their rich and surprising journey across the United States. Through Huies eyes, keenly aware of his own Midwestern roots and perspective, we witness such images as a Vietnamese Elvis, Miss Congeniality on her cell phone in San Franciscos Chinatown, a Hm.